Knowledge, Self-Management, and Reduction of Stress Levels in Adhering to a Diabetes Mellitus Diet at Bhayangkara Mohamad Hasan Hospital, Palembang - Alvian Harisandy; Selamat Parmin (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder with an increasing prevalence each year, leading to several severe consequences. A crucial aspect of diabetes care is dietary management; however, adherence to a diet often causes stress in patients. Self-management knowledge and competency contribute significantly to a patient's ability to reduce stress and improve the success of a diet regimen. The purpose of this community service is to improve knowledge of diabetes diet, diabetes self-management, and reduce stress levels in type 2 DM patients. The methods used are lectures, discussions, and educational videos. Before and after the community service, questionnaires were administered regarding diabetes diet knowledge, diabetes self-management, and stress levels in following the diet. The results of the community service showed an increase in knowledge of diabetes diet (the average increase in diabetes diet knowledge score was 23.4 + 5.2), diabetes self-management (the average increase in diabetes self-management score was 7.1 + 3.23), and a decrease in stress levels (the average decrease in score was 13.4 + 4.21) in type 2 DM patients. Indirectly, this community service activity will improve the quality of life and well-being of type 2 DM patients at Bhayangkara Mohamad Hasan Hospital, Palembang.